AB1101 ANA SUBSETS ANTIBODY PROFILE OF EARLY UNDIFFERENTIATED ARTHRITIS (UA) IN PAKISTAN. (June 2019) - Azhar Rizvi, Syed Hussain; Aneela Pasha, Tariq Gazdar; Saeed, Mohammad
Abstract : Background: Undifferentiated Arthritis (UA) is a group of inflammatory disorders where early synovitis (duration less than 12 months) is present, however patients do not meet criteria for established rheumatologic disorders such as Rheumatoid arthritis, Lupus or Spondyloarthritis (1). On long term follow up, a subpopulation of UA patients converge into definitive Rheumatologic disorders. Up to 50% of early arthritis in European cohorts has been reported to be UA (1, 2). Objectives: Identify Anti-nuclear antibody (ANA) Subset antibodies in patients presenting with early UA. Methods: Over a 1-year period (2017-18) patients with early UA were prospectively evaluated. This included clinical exam, routine laboratory investigations including ESR and CRP, RF and anti-CCP as well as Musculoskeletal ultrasound (MSKUS) (3). These patients underwent further testing for ANA Subset antibodies. ANA subsets (17 antibodies) were performed using standard immunoblot assays (EUROIMMUN) at our clinical laboratory (4). Results: 110 UA patients were found to have positive ANA subsets. The most frequent antibodies were Ku (77.3%) and Mi2 (73.6%) followed by dsDNA (30%) and Nucleosome antibody (29%) (Figure 1 ). Low frequency antibodies included Sm (n=1), Ribosomal-P and PCNA (n=2 each), Jo-1 (n=3), PM-Scl100 (n=4) and SSB (n=5), whereas Scl70 antibodies were absent. SSA (n=9) and Ro-52 (n=14) together constituted 21% frequency. These antibodies had high signal intensities (mean ± SD SSA = 52±35 and Ro-52 = 46±25). Ku (17±11) and Mi2 (22±15) had modest signal intensities (Figure 2 ). Clinically 42 patients were classified as RA (RF+ = 33%; anti-CCP+ = 14%) and 41 patients met ACR criteria for SLE while 2 patients met criteria for both and were classified as Rhupus. ANA subset antibody frequencies did not statistically differ between the RA and SLE groups signifying that the clinically classified RA patients in fact had early Rhupus which did not meet ACR criteria for SLE. Conclusion: Early UA is difficult to categorize clinically, sometimes even after long term follow up, though a substantial portion converge into RA. This study shows that there is a significant portion of early Rhupus in the RA group whose steroid discontinuation leads to a disease flare. ANA Subset antibody profile in such patients may help in their more accurate diagnoses and treatment. References: [1] van Aken J, van Bilsen JH, Allaart CF, Huizinga TW, Breedveld FC. The Leiden Early Arthritis Clinic. Clin Exp Rheumatol. 2003 Sep-Oct;21(5 Suppl 31):S100-5. PMID: 14969059. [2] Hülsemann JL, Zeidler H. Undifferentiated arthritis in an early synovitis out-patient clinic. Clin Exp Rheumatol. 1995 Jan-Feb;13(1):37-43. PubMed PMID: 7774101. [3] Horton SC, Tan AL, Wakefield RJ, Freeston JE, Buch MH, Emery P. Ultrasound-detectable grey scale synovitis predicts future fulfilment of the 2010 ACR/EULAR RA classification criteria in patients with new-onset undifferentiated arthritis. RMD Open. 2017;3(1):e000394. PMID: 28469936. [4] Op De Beéck K, Vermeersch P, Verschueren P, Westhovens R, Mariën G, Blockmans D, Bossuyt X. Antinuclear antibody detection by automated multiplex immunoassay in untreated patients at the time of diagnosis. Autoimmun Rev. 2012;12(2):137-43. PMID: 22387973.5. Disclosure of Interests: Syed Hussain Azhar Rizvi Grant/research support from: Participation in EULAR 2019 Meeting is sponsored by Searle Pak, Tariq Gazdar Shareholder of: Partner at ImmunoCure which performs Autoimmune Disease testing, Aneela Pasha: None declared, Mohammad Saeed Shareholder of: Partner at ImmunoCure - laboratory, which performs Autoimmune antibody testing, Grant/research support from: Participation in EULAR 2019 Meeting is sponsored by High-Q Pharma Pak